2021
DOI: 10.1002/adhm.202102073
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Multifunctional Nanoenzyme Tailored for Triggering Tumor Microenvironment Activated NIR‐II Photoacoustic Imaging and Chemodynamic/Photothermal Combined Therapy

Abstract: The accurate diagnosis and targeted therapy of malignant tumors face significant challenges. To address these, an oxidized molybdenum polyoxometalate-copper nanocomposite (Ox-POM@Cu) is designed and synthesized here. The doping with Cu determines the formation of oxygen vacancies, which can increase the carrier concentration in Ox-POM@Cu, accelerate electron transfer, and enhance the redox activity, thus playing an efficient catalytic role. The nanocomposite presents unique enzymatic functions characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…On the other hand, Cu 2+ doping increases the formation of oxygen vacancies, accelerates the electron transfer of MIL-100(Fe) and enhances the redox activity, thus accelerating the reduction of Fe 3+ to Fe 2+ , and thereby can produce more ˙OH and play an effective catalytic role (eqn (8)). 47,48…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Cu 2+ doping increases the formation of oxygen vacancies, accelerates the electron transfer of MIL-100(Fe) and enhances the redox activity, thus accelerating the reduction of Fe 3+ to Fe 2+ , and thereby can produce more ˙OH and play an effective catalytic role (eqn (8)). 47,48…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Cu 2+ doping increases the formation of oxygen vacancies, accelerates the electron transfer of MIL-100(Fe) and enhances the redox activity, thus accelerating the reduction of Fe 3+ to Fe 2+ , and thereby can produce more • OH and play an effective catalytic role (eqn (8)). 47,48 In consideration of the relatively weak red UCL of UC that might be not enough to trigger efficient PDT of Ce6, a 671 nm laser (15 mW cm −2 ) was introduced to evaluate the PDT capacity of UCTSCF. 1 O 2 is able to react with DPBF and induce obvious DPBF fading.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Moreover, in the presence of reductive TME, there was a significant enhancement in the NIR absorption of SPB@POM, leading to a further improvement in the PAI contrast and PTT efficacy. Similarly, Wang et al developed an oxidized molybdenum polyoxometalate-copper nanocomposite (Ox-POM@Cu) as a multifunctional nanozyme that displayed glutathione peroxidase (GSH-PX) and catalase (CAT) activities . Under the trigger of endogenous GSH, the doped Mo 6+ and Cu 2+ in Ox-POM@Cu would be reduced into Mo 5+ and Cu + , respectively, and simultaneously activate the absorbance of POM in the NIR-II section for responsive PAI and PTT.…”
Section: Photoacoustic Imaging-guided Tumor Therapymentioning
confidence: 99%
“…Similarly, Wang et al developed an oxidized molybdenum polyoxometalatecopper nanocomposite (Ox-POM@Cu) as a multifunctional nanozyme that displayed glutathione peroxidase (GSH-PX) and catalase (CAT) activities. 182 Under the trigger of endogenous GSH, the doped Mo 6+ and Cu 2+ in Ox-POM@ Cu would be reduced into Mo 5+ and Cu + , respectively, and simultaneously activate the absorbance of POM in the NIR-II section for responsive PAI and PTT. Moreover, the obtained Cu + could occur in a Fenton-like reaction with H 2 O 2 with a fast reaction rate to produce hydroxyl radical (•OH) and achieve CDT.…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…Although CDT is effective in preventing tumor growth and metastasis, it doesn’t have the ability to completely eliminate the tumor because of insufficient endogenous H 2 O 2 ( Liu Y. et al, 2020 ; Ji S. et al, 2021 ). Thus, oxygen vacancy-promoted synergistic PTT/CDT or PTT/PDT/CDT have been explored to achieve the satisfactory anticancer efficacy, so as to effectively eliminate tumor and inhibit tumor recurrence ( Ji et al, 2019 ; Peng et al, 2020 ; Sun et al, 2020 ; Ji X. et al, 2021 ; Kong et al, 2021 ; Zhang et al, 2021 ; Wang et al, 2022 ; Zhou et al, 2022 ). For instance, Tan et al ( Zhou et al, 2022 ) reported the dark-blue co-intercalated MoO 3− x (denoted as NH−MoO 3− x ) nanobelts via the ball-milling process and then aqueous Na + /H 2 O co-intercalation as efficient nanozymes for photothermal-enhanced CDT.…”
Section: Vacancy Defective Nanomaterials-enhanced Phototherapy and Mu...mentioning
confidence: 99%